A Successful Vancomycin Treatment of Multidrug-Resistant MRSA-Associated Canine Pyoderma - Foglia Manzillo, Valentina; Paola Nocera, Francesca; De Martino, Luisa; Gizzarelli, Manuela; Oliva, Gaetano (Journal of Dermatologic Research And Therapy, 2016)
Case Report This report describes a case of diffuse pyoderma in a 10-year-old female dog with hypothyroidism. A previous treatment, without an early diagnosis, including cephalosporin associated with prednisolon resulted to be unsuccessfully. After clinical and microbiological examination in our laboratories, a diagnosis of methicillinresistant Staphylococcus aureus (MRSA)-associated pyoderma was made. The antimicrobial susceptibility testing evidenced many resistances and susceptibility of the strain only to vancomycin and linezolid. A new therapy against hypothyroidism and associated with an appropriate antimicrobial (vancomycin) treatment, improved and resolved the infection. Clinical Significance To our knowledge, this is the first case of canine pyoderma caused by a strain of MRSA with a such severe multiresistant profile. MRSA infections present a serious challenge because of the emergence of resistance to numerous conventional antibiotics and the risk factors associated with the transfer of the bacteria to humans, who have a contact with infected pets.
Keywords: methicillin-resistant Staphylococcus aureus; canine pyoderma; hypothyroidism; vancomycin.